Augmented capacity for peripheral serotonin release in human obesity. Issue 11 (November 2018) - Young, Richard; Lumsden, Amanda; Martin, Alyce; Schober, Gudrun; Pezos, Nektaria; Thazhath, Sony; Isaacs, Nicole; Cvijanovic, Nada; Sun, Emily; Wu, Tongzhi; Rayner, Christopher; Nguyen, Nam; et al.
Abstract Background/objectives Evidence from animal studies highlights an important role for serotonin (5-HT), derived from gut enterochromaffin (EC) cells, in regulating hepatic glucose production, lipolysis and thermogenesis, and promoting obesity and dysglycemia. Evidence in humans is limited, although elevated plasma 5-HT concentrations are linked to obesity. Subjects/methods We assessed (i) plasma 5-HT concentrations before and during intraduodenal glucose infusion (4 kcal/min for 30 min) in non-diabetic obese (BMI 44 ± 4 kg/m2, N = 14) and control (BMI 24 ± 1 kg/m2, N = 10) subjects, (ii) functional activation of duodenal EC cells (immunodetection of phospho-extracellular related-kinase, pERK) in response to glucose, and in separate subjects, (iii) expression of tryptophan hydroxylase-1 (TPH1 ) in duodenum and colon (N = 39), and (iv) 5-HT content in primary EC cells from these regions (N = 85). Results Plasma 5-HT was twofold higher in obese than control responders prior to (P = 0.025), and during (iAUC, P = 0.009), intraduodenal glucose infusion, and related positively to BMI (R 2 = 0.334, P = 0.003) and HbA1c (R 2 = 0.508, P = 0.009). The density of EC cells in the duodenum was twofold higher at baseline in obese subjects than controls (P = 0.023), with twofold more EC cells activated by glucose infusion in the obese (EC cells co-expressing 5-HT and pERK, P = 0.001), while the 5-HT content of EC cells in duodenum and colon was similar;TPH1 expression was 1.4-fold higher in the duodenum of obese subjects (P = 0.044), and related positively to BMI (R 2 = 0.310, P = 0.031). Conclusions Human obesity is characterized by an increased capacity to produce and release 5-HT from the proximal small intestine, which is strongly linked to higher body mass, and glycemic control. Gut-derived 5-HT is likely to be an important driver of pathogenesis in human obesity and dysglycemia.